Solve the system of equations:
y=x^2 + 9
y=6x
How do I do these?
6 answers
Solve the system of equations:
y=4x+8
x^2 + 7x - 20
y=4x+8
x^2 + 7x - 20
Y = x^2 + 9.
Y = 6x.
In Eq1, replace Y with 6x:
6x = x^2 + 9.
x^2 - 6x + 9 = 0.
Solve the Quadratic Eq .
Y = 6x.
In Eq1, replace Y with 6x:
6x = x^2 + 9.
x^2 - 6x + 9 = 0.
Solve the Quadratic Eq .
So wait would x^2 - 6x + 9 = 0 be the answer for number 1?
Y = 4x + 8.
Y = x^2 + 7x - 20.
In Eq2, replace Y with 4x + 8:
4x + 2 = x^2 + 7x - 20.
x^2 + 3x - 22 = 0.
Solve using Quadratic Formula:
X = (-B +- sqrt(B^2-4AC))/2A.
X = (-3 +- sqrt(9 + 88))/2 = 3.42, and -6.42.
Y = x^2 + 7x - 20.
In Eq2, replace Y with 4x + 8:
4x + 2 = x^2 + 7x - 20.
x^2 + 3x - 22 = 0.
Solve using Quadratic Formula:
X = (-B +- sqrt(B^2-4AC))/2A.
X = (-3 +- sqrt(9 + 88))/2 = 3.42, and -6.42.
1.x^2 - 6x + 9 = 0.
Solve the Eq. by factoring:
9 = -3 * -3.
(x-3) (x-3) = 0,
x-3 = 0, X = 3.
3 should satisfy both of your given Eqs.
Solve the Eq. by factoring:
9 = -3 * -3.
(x-3) (x-3) = 0,
x-3 = 0, X = 3.
3 should satisfy both of your given Eqs.